The prevalence of premenstrual syndrome in young woman - Kozłowski, Piotr; Kozłowska, Magdalena; Kozłowska, Karolina; Cisło, Magdalena (Journal of Education, Health and Sport, 2017)
Regular menstrual cycles reflect the condition of a woman's health. However, they are influenced by many external factors. Premenstrual Syndrome (PMS) is a syndrome of somatic and mental symptoms including irritability, fatigue, irritability, depression, crying, self-deprecation, breast hypersensitivity, feeling water retention, diarrhea and constipation, headaches. These symptoms are most noticeable at the age of 25-35. The aim of the study was to evaluate premenstrual syndrome prevalence in young, healthy women. The questioned women were also asked about education, age, premenstrual syndrome, oral contraceptives, pain during menstruation and the frequency of visits to a gynecologist. The study included 122 female participants. The age of participants ranged from 16 to 45 years. The study conducted in the period from January 2017 to April 2017 and it employed standardized interview research method. Research tool, which was used for data collection was a questionnaire consisted of 19 questions single-choice questions and 3 multiple-choice questions.. Statistical analysis was performed using the chi-square test. All values for which p <0.05 (probability of error) were considered statistically significant. Respondents were asked about education, work and knowledge about eye diseases. All respondents reported premenstrual symptoms, and 26.2% indicated that they felt PMS symptoms regularly or frequently (48.4%). 72.1% (p <0.05) of the questioned women considered that the most severe symptoms of PMS were psychological. Emotional depression affects 73.8% of respondents, the feeling of self-esteem affects or anxious affects 52.5% of respondents. Concentration problems were reported by 23.8% of respondents. The most common somatic symptom of PMS was water retention (69.8%). Respondents also indicated that they have more problems with their complexion (45.9%).